A Population‐Based Approach to Reporting System–Level Performance Measures for Rheumatoid Arthritis Care. Issue 5 (11th May 2021) - Barber, Claire E. H.; Marshall, Deborah A.; Szefer, Elena; Barnabe, Cheryl; Shiff, Natalie J.; Bykerk, Vivian; Homik, Joanne; Thorne, J. Carter; Ahluwalia, Vandana; Benseler, Susanne; Mosher, Dianne; Twilt, Marinka; et al.
Abstract : Objective: To operationalize and report on nationally endorsed rheumatoid arthritis (RA) performance measures (PMs) using health administrative data for British Columbia (BC), Canada. Methods: All patients with RA in BC ages ≥18 years were identified between January 1, 1997 and December 31, 2009 using health administrative data and followed until December 2014. PMs tested include: the percentage of incident patients with ≥1 rheumatologist visit within 365 days; the percentage of prevalent patients with ≥1 rheumatologist visit per year; the percentage of prevalent patients dispensed disease‐modifying antirheumatic drug (DMARD) therapy; and time from RA diagnosis to DMARD therapy. Measures were reported on patients seen by rheumatologists, and in the total population. Results: The cohort included 38, 673 incident and 57, 922 prevalent RA cases. The percentage of patients seen by a rheumatologist within 365 days increased over time (35% in 2000 to 65% in 2009), while the percentage of RA patients under the care of a rheumatologist seen yearly declined (79% in 2001 to 39% in 2014). The decline was due to decreasing visit rates with increasing follow‐up time rather than calendar effect. The percentage of RA patients dispensed a DMARD was suboptimal over follow‐up (37% in 2014) in the total population but higher (87%) in those under current rheumatologist care. The median time to DMARD in those seen by a rheumatologist improved from 49 days in 2000 to 23 days in 2009, with 34% receiving treatment within the 14‐day benchmark. Conclusion: This study describes the operationalization and reporting of national PMs using administrative data and identifies gaps in care to further examine and address.